2014
DOI: 10.1002/jmri.24547
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the lenz effect on heart valve prostheses at 1.5 T

Abstract: This study provides empirical evidence of the Lenz Effect on cardiac valve prostheses exposed to the MR B0 field causing functional valve impedance and increasing the risk of valvular regurgitation and reduced cardiac output. Thus, it is essential to consider the potential for the Lenz Effect when scanning cardiac valve implant patients in order to safeguard their wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The interaction between both mechanical and biological valve prostheses and magnetically induced electric currents has been demonstrated [34]. …”
Section: Discussionmentioning
confidence: 99%
“…The interaction between both mechanical and biological valve prostheses and magnetically induced electric currents has been demonstrated [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Golestanirad et al [14] concluded that the effect of induced vibration through gradient switching can be neglected because of the small amplitudes of the gradient fields. Edwards et al [15] built a flow rate setup to investigate potential flow rate irregularities of heart valves. These experiments revealed flow irregularities when valves were moved in the fringe field.…”
Section: Introductionmentioning
confidence: 99%